Ethylene oxide induces central-peripheral distal axonal degeneration of the lumbar primary neurones in rats. Issue 6 (June 1985) - Ohnishi, A; Inoue, N; Yamamoto, T; Murai, Y; Hori, H; Koga, M; Tanaka, I; Akiyama, T
Abstract : Wistar rats subjected to a single exposure lasting six hours to ethylene oxide (EO) at a concentration of 500 parts per million three times a week for 13 weeks developed ataxia in the hindlegs. Myelinated fibres in hindleg nerves and in the fasciculus gracilis showed axonal degeneration sparing the nerve cell body of the lumbar dorsal root ganglion and myelinated fibres of lumbar dorsal and ventral roots. These pathological findings are compatible with central-peripheral distal axonal degeneration. This is the first animal model of EO neuropathy to be histopathologically verified.